The position of LDCs in foreign trade - Günther Weinert (Intereconomics, 1971)
Recent negotiations about selling prices for crude oil have reflected an economic controversy between developing countries and the industrialised nations of the West. That, in this particular case, the demands raised by developing countries had to be accepted almost entirely was due to their strong position in the international market for oil. However, such strength In the market is not at all typical for most developing countries.
Keywords: 330; Development policy